Incidence and injury mechanism of ACL injury in tennis player - Yonetani, Y.; Nakata, K. (Medicine and Science in Tennis, 2009)
BACKGROUND: The incidence of anterior cruciate ligament (ACL) injury is lower in tennis than in other sports such as basketball and soccer. Although the mechanisms of ACL injury during sport activities has been defined in some extent, those in tennis are not clear. PURPOSE: To retrospectively examine the incidence of ACL injury and explore the mechanisms of ACL injury in tennis based on medical records and questionnaires. METHODS: Medical records of the patients with ACL injuries who received reconstruction surgery in our institutions were reviewed and the number of patients of ACL injury in tennis was counted. The situation, player behavior, and joint kinematics at the time of ACL injury were analyzed from clinical record. RESULTS: There were 7 cases among 272 (2.6%) of ACL reconstruction during 3 years. There was no contact injury. Two common mechanisms were identified in tennis. The most common situation was plant-and-cut movement, such as chasing backward and hit in a backhand stroke or chasing forward to hit a short ball. The other common mechanism was a single leg landing with off balance after a jumping smash or volley. CONCLUSION: Among 272 cases of ACL reconstruction, there were 7 cases (2.6%) of ACL tear during playing tennis. Plant-and-cut and landing with unbalanced were two common mechanisms during playing tennis. CLINICAL RELEVANCE: Control the knee position avoiding plant-and-cut movement or landing with unbalanced should be directed to prevent from ACL injuries during playing tennis.